Busulfan Treatment Effects on Testicular Tissue and Serum Levels of Anti- Mullerian Hormone and Testosterone in Adult Mice - Arash Payehdar; Ebrahim Hosseini; Davood Mehrabani; Mohsen Forouzanfar (The Prodia Education and Research Institute (PERI), 2017)
BACKGROUND: Busulfan, a chemotherapeutic drug, is an alkylating antineoplastic agent that belongs to the class of alkyl sulfonates and has some side effects on fertility. This research was aimed to investigate the effects of busulfan on testicular tissue and serum levels of anti-Mullerian hormone (AMH) and testosterone in adult mice.METHODS: Eighteen adult male Balb/C mice were collected randomly and were assigned in three groups including; control, azoospermia and spontaneous recovery. The groups, except for control group, received two injections of busulfan (10 mg/kg) intraperitoneally with 21-days interval in order to induce azoospermia. Thirty-five and 140 days after the last injection, the effects of busulfan on testicular tissue were evaluated by histologic, histomorphometric and hormonal changes. AMH and testosterone were measured by enzyme-linked immunosorbent assay (ELISA) and radioimmunoassay (RIA) kits, respectively.RESULTS: Hormonal analyses showed no significant differences in AMH and testosterone serum levels. Histologic and histomorphometric evaluation showed disrupted spermatogenesis in azoospermia group, and restoration of spermatogenesis spontaneously in spontaneous recovery group.CONCLUSION: Busulfan at doses was used had no effect on AMH and testosterone serum levels. Busulfan can also induce azoospermia on a temporary basis however, in long term, spontaneous recovery can occur. The results indicated that some side effects are reversible and may depend on the dose applied.KEYWORDS: Busulfan, anti-Mullerian hormone, testosterone, mouse, testis